Educating the spiritual and social life of the community post- pandemic in Danukusuman Village, Surakarta - Suratno Suratno; Baihaqi Maulana Hakim; Umi Khoiriyah; Muhammad Syaifuddin Zuhry; Zidni Fahma (Community Empowerment, 2023)
People in the Danukusuman Village, Surakarta are facing various problems in various sectors of life due to the pandemic, which has caused the community's stress level to increase. When the Covid 19 pandemic subsided, people began to move and rise from adversity. Spiritual and social intelligence is very important for people to come up calmly and full of hope. This community service aims to educate the spiritual and social life of the people in the Danukusuman village, Surakarta. The center of this program is at the Tjokrosoekarno Danukusuman Mosque. The methodology in this community service is community education using lectures, discussions, social services, teaching, training, tablig akbar, and environmental observations. The result of this program is the intelligence in their spiritual life increases. This can be seen from their increasing ability in reading the Qur'an and increasing Islamic insight. Likewise, the social life of the community is getting better, with the existing social activities. With a good spiritual and social life, it is easier for people to rise up post- pandemic.